PTU-128 Prevalence and Management of Irritable Bowel Syndrome Seen in Colorectal Surgery and Gastroenterology Clinics. (17th August 2016) - Shearer, J; Luthra, P; Ford, AC
Abstract : Introduction: Irritable bowel syndrome (IBS) in the UK accounts for a large proportion of patients seen in secondary care. Pathways to the diagnosis of IBS are not standardised, and patients are often reviewed outside a luminal Gastroenterology service. We examined the burden of IBS in both Colorectal Surgery and Gastroenterology clinics. Methods: All patients seen with IBS in either Gastroenterology (GE) or Colorectal Surgery (CS) clinics over a 1 month period January to February 2014 at Leeds Teaching Hospitals NHS Trust were identified. The following data were retrospectively recorded: age/sex of the patient, investigations prior to diagnosis, number of visits to that speciality clinic, number and type of medications prescribed, and final placement of the patient. We compared management of patients in both settings using a Chi-squared test. Results: There were a total of 76 patients with IBS seen in CS clinics (mean age 49.6 years, 39 (51.3%) female) and 57 patients in GE clinics (mean age 39.1 years, 39 (68.4%) female). The number and type of investigations requested prior to diagnosis are detailed in Table 1 . In CS clinics, colonic imaging (colonoscopy, sigmoidoscopy or barium enema) was requested in 70 (92.1%) patients, compared with 39 (68.4%) patients in GE clinics (P = 0.001). Cross-sectional imaging was utilised in 36 (47.4%) patients in CS clinics, compared with 19 (33.3%) patients in GE clinics (P = 0.15). Serological testing for coeliac disease was not performed in 22 (29.9%) patients in CS clinics, and 5 (8.8%) patients in GE clinics (P = 0.008). For the CS clinic patients the mean number of visits was 2.7 (range 1–14) with 22 (28.95%) patients offered prescribed therapy. In the GE clinic patients the mean number of visits was 2.5 (range 1–5), with 43 (75.4%) patients offered prescribed therapy (P < 0.001). Nine (11.8%) patients were seen by both services. Twenty-six (45.6%) patients were referred to a dietician from the GE clinic, but none from the CS clinic (P < 0.001). No patients were referred for hypnotherapy or psychological therapy from either clinic. Conclusion: These data highlight the need for a more consistent referral process, and a more specialised approach to the management of this patient group. This should be based on current guidelines for the management of IBS using evidence-based treatments and with easy access to dietetic, psychological, and specialist nurse support. Disclosure of Interest: None Declared